Analisis Penentuan Indeks Bahaya Erosi di Sub DAS Sekayam - Liehan, James; Gunarto, Danang; Soeryamassoeka, Stefanus Barlian (Universitas Tanjungpura, 2025)
The Sekayam River, the main and longest river in the Sekayam Watershed (DAS Sekayam), plays a strategic role in supporting the livelihoods of local communities. Erosion not only disrupts the activities of local communities along the riverbanks but also increases the risk of flooding and worsens environmental conditions. This study aims to: (1) Identify the factors contributing to the rate of erosion in the Sekayam Sub-Watershed, (2) Determine the level of erosion hazard/erosion rate using the Universal Soil Loss Equation (USLE) method and assess the erosion hazard index in the Sekayam Sub-Watershed, and (3) Develop an erosion hazard index map for the Sekayam Sub-Watershed, illustrating the classification and severity of erosion hazards using ArcGIS software.This study analyzes the erosion hazard index in the Sekayam Sub-Watershed using the USLE method, which considers factors such as rainfall erosivity (R), soil erodibility (K), slope length and steepness (LS), land management (C), and conservation practices (P). Based on the analysis, the Sekayam Sub-Watershed has an average annual rainfall of 3,058.94 mm, with dominant soil types being Ultisol (86%) and Inceptisol (14%), and mostly flat slopes (61.75%). These factors influence the erosion hazard level, which is classified as very high, particularly in land cover types such as mixed dryland agriculture with shrubs. The erosion hazard index mapping results show an average IBE value of 7.9510, indicating a high level of erosion risk.